Unusual diagnostic findings in temporal lobe epilepsy: A combined MRI and 18F-dopa case study. (2020) - Feraco, Paola; Donner, Davide; Picori, Lorena; Rozzanigo, Umberto
Highlights: Onset Temporal Lobe Epilepsy may mimic a low-grade tumor at conventional MRI. Arterial Spin Labeling likely detect the epileptogenic focus even beyond 24 h after seizures. The knowledge of electroencephalographic findings is necessary when interpreting brain areas of tracer uptake. 18F-DOPA uptake may represent increased dopamine transport induced by seizures. 18F-DOPA tracer uptake is not always related to malignancy. Abstract: Temporal lobe epilepsy is the most common focal epilepsy in adults and often causes pharmacoresistant seizures. Magnetic resonance imaging (MRI) and PET studies have widely demonstrated a number of morphological and molecular abnormalities in epilepsy. However, considering the dopaminergic system, only a bilateral 18 F-DOPA uptake reduction within the basal ganglia has been described. We report the unusual finding of increased 18 F-DOPA uptake in a patient with focal recurrent seizures and "deja vu" experiences in the setting of cortical swelling detected at MRI exam. The final diagnosis was in in keeping with hippocampal sclerosis, confirmed during follow-up MR exams. In this case 18 F-DOPA uptake may represent increased dopamine transport induced by seizures. Nuclear medicine physicians and radiologists should be aware of clinical and electroencephalographic findings when interpreting brain areas of tracer uptake, which are not always related to malignancy.